Prevalensi trematoda gastrointestinal pada sapi di pasar ternak payakumbuh - Delli Lefiana; Dihan Kurnia; Sujatmiko Sujatmiko; Prima Silvia Noor; Engki Zelpina; Rizki Ardyes (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2022)
This study aims to determine the prevalence of trematoda infection in the gastrointestinal tract in cattle at the Payakumbuh Livestock Market. The research was conducted in August 2020. The method used was a survey using purposive sampling method. A total of 155 stool samples from the Paykumbuh Livestock Market were examined using floating and sedimentation method. Analyze the data in the form of qualitative descriptive analysis. The gastrointestinal flukes found were Fasciola sp and Paramphistomum sp. The most common fluke found was Fasciola sp. in cows is 16.15% and bulls is 12%. Infection with 1 species of fluke in 22.10% of cows and 16% of bulls. Infection with 2 species of fluke in 3.38% of cows and 4% of bulls. The prevalence of tapeworm infection in the 0-2 years old group was 23.61% and the >2 year old group was 20.48%.